Morphological quantification of aortic calcification from low magnification images - Angulo, Jesús (Image analysis and stereology, 2003)
Atherosclerotic and medial vascular calci cations are frequent in chronic renal failure patiens and predict their increased cardiovascular mortality. Experimental models for mice have been recently developed in order to study these disorders. The aim of this paper is to present the morphological image processing algorithms developed for the semi-automated measurement of calci cation from sections of aorta stained using von Kossa's silver nitrate procedure and acquired at low magni cation power (x 2.5) on colour images. Theapproach is separated into two sequential phases. First, the segmentation is aimed to extract the calci cation structures and on the other hand to demarcate the region of the atherosclerotic lesion within the tissue. The segmentation yields the image data which is the input to the second phase, thequanti cation. Calci ed structures are measured inside and outside the lesion using a granulometric curve which allows the calculation of statisticalparameters of size. The same operator computes the shape of the lesion. The relative proportion of the area of calci cation is also calculatedrespectively for the atherosclerotic lesion area and the area outside such lesions. In conclusion, the here developed method allows quanti cation of vascular calci ed deposits in mouse aorta. This method will be useful for the quantitative assessment of pathological vascular changes in animals and man.
Keywords: Aorta; Atherosclerosis; Kalcinoza; Pathology; Kidney Failure, Chronic; Ledvica, odpoved kronična; Anatomy And Histology; Miši Knockout; Slika, obdelava z računalnikom; Calcinosis; Srebrenje; Mice, Knockout; Silver Staining; ateroskleroza; Image Processing, Computer-Assisted; miši; ledvice